Битемплатный синтез и структурно-адсорбционные характеристики мезопористых цеолитов, полученных на основе Al-аэросилов - Хоменко, K.Н.; Жуков, Г.И.; Горников, Ю.И.; Брей, В.В. (Поверхность, 2007)
Предложен метод одностадийного битемплатного синтеза мезопористых цеолитсодержащих материалов на основе Al-аэросилов, исследована кинетика их образования и структурно-текстурные свойства. Полученные материалы охаракте-ризованы методами ИК-спектроскопии, рентгенографии и адсорбции азота. Показано, что образование цеолитных структур (до ~25%) не сопровождается разрушением мезофазной структуры и происходит в стенках мезопор. A method has been proposed of the one-stage bitemplate synthesis of mesoporous zeolite containing materials on the basis of Ti-aerosil (Ti-MZ), also the kinetics is studied of their formation and texture features. The materials obtained have been characterized by methods of IR-spectroscopy (FTIR), X-ray diffraction (XRD) and adsorption of nitrogen. Formation of the zeolite structures (till ~25%) is not accompanied with the destruction of mesophase structure and happens in the mesopores walls.